2006
DOI: 10.1186/1471-2474-7-91
|View full text |Cite
|
Sign up to set email alerts
|

Increased endothelin-1 and diminished nitric oxide levels in blister fluids of patients with intermediate cold type complex regional pain syndrome type 1

Abstract: Background: In complex regional pain syndrome type 1 (CRPS1) pro-inflammatory mediators and vascular changes play an important role in the sustained development and outcome of the disease. The aim of this study was to determine the involvement of vasoactive substances endothelin-1 (ET-1) and nitric oxide (NO) during early chronic CRPS1. Methods:Included were 29 patients with CRPS 1 who were diagnosed during the acute stage of their disease and observed during follow-up visits. Disease activity and impairment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 48 publications
(60 reference statements)
3
119
3
3
Order By: Relevance
“…Elevations of several cytokines have been observed in patients suffering from CRPS (Groeneweg et al 2006). Our data, however, demonstrated that anti-NGF actually increases the abundance of TNFα, IL-1β and the anti-inflammatory IL-10 while leaving the concentration of IL-6 unchanged in the hind paw skin of rats after fracture despite reductions in nociceptive sensitization.…”
Section: Discussioncontrasting
confidence: 41%
“…Elevations of several cytokines have been observed in patients suffering from CRPS (Groeneweg et al 2006). Our data, however, demonstrated that anti-NGF actually increases the abundance of TNFα, IL-1β and the anti-inflammatory IL-10 while leaving the concentration of IL-6 unchanged in the hind paw skin of rats after fracture despite reductions in nociceptive sensitization.…”
Section: Discussioncontrasting
confidence: 41%
“…However, it should be noted that in clinical practice it is common to observe atypical responses to pharmacological interventions in those with CRPS; for example, an increased sensitivity to a drug such that only low doses are tolerated. Recently, increasing evidence of raised cytokine activity (Huygen et al 2002;Groeneweg et al 2006) and autoantibodies in CRPS (Blaes et al 2004;Goebel et al 2005;Kohr et al 2009Kohr et al , 2011 have encouraged consideration of different treatment approaches. Case study data suggests anti-TNF therapy may have a role in CRPS (Ozgül et al 2011) but controlled trial data is still awaited.…”
Section: Pharmacologicalmentioning
confidence: 99%
“…Routine serology markers for inflammation are not raised in CRPS, though recent analysis of blister fluid from CRPS affected limbs has shown elevated inflammatory markers (Huygen et al 2002;Groeneweg et al 2006). These changes in cytokine activity are not associated with disease duration or other clinical signs but appear to be related specifically to the degree of mechanical hyperalagesia, rather than pain per se, as they remain high even when the pain disappears (Wesseldijk et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…47,94 Both Foisie and Evans described arterial vasospasms, and recent evidence indicates that CRPS limbs exhibit both reduced nitricoxide 33 and enhanced vasoconstrictor responsiveness to norepinephrine. 2,7,16,89 Importantly, the main cause of arterial vasospasm or enhanced vasoconstriction following IR injury is the dramatic loss of nitric oxide (much of which is scavenged by increased oxygen-free radicals to produce nitrogen-free radicals).…”
Section: Role Of Microvascular Dysfunctionmentioning
confidence: 99%